In vivo imaging neurotransmitter function - Nikolaus, S.; Larisch, R.; Vosberg, H.; Beu, M.; Hautzel, H.; Wirrwar, A.; Mueller, H.-W.; Antke, C. (Nuklearmedizin - NuclearMedicine, 2011)
This article gives an overview of those small animal imaging studies which have been conducted on neurotransmitter function in the rat 6-hydoxydopamine (6-OHDA) model of Parkinson’s disease, and discusses findings with respect to the outcome of clinical studies on Parkinsonian patients.
Keywords: Parkinson's disease; PET; SPECT; dopamine; 6-hydroxydopamine model; small animal imaging